Leg extension force-velocity imbalance has negative impact on sprint performance in ball-game players - Junge, N.; Morin, J.-B.; Nybo, L. (Sports Biomechanics, 2020)
Ballistic actions are imperative in sports where performance depends on power production across a relevant range of contraction- and movement velocities. Force-velocity-power (FvP) profiling provides information regarding neuromuscular capabilities and vertical performances, but knowledge regarding its associative value towards horizontal movements is scarce. Therefore, we conducted FvP profiling and analysed associations with uni- and multidirectional ballistic performance tasks in 27 international- to national-level athletes (18.9 ± 2.6 years, 182.9 ± 7.1 cm and 79.2 ± 11.9 kg). Low to moderate correlations were observed between theoretical maximal power (Pmax) and horizontal acceleration (R = -0.43), speed (R = -0.64), sprint (R = -0.60) and agility (R = -0.59) performances. Force-velocity imbalance (FvIMB) significantly (P = 0.05) strengthened the correlations towards sprinting ability (from -0.60 to -0.74) and agility (from -0.59 to -0.68), however, both correlations remaining weaker than for jumping performances (R = 0.78-0.86). In conclusion, FvP profiling provides information of importance for horizontal and vertical performances with a significant positive effect of Pmax, but negative effect of FvIMB. Assessment of lower-extremity neuromuscular capabilities through FvP profiling and associated development of training programmes targeting compensation of either force- or velocity deficit may benefit the ability to utilise a given power potential.